Cancer Information Seeking in the Digital Age: Effects of Angelina Jolie's Prophylactic Mastectomy Announcement. (January 2015) - Noar, Seth M.; Althouse, Benjamin M.; Ayers, John W.; Francis, Diane B.; Ribisl, Kurt M.
Objective . This study used digital surveillance to examine the impact of Angelina Jolie's prophylactic mastectomy announcement on cancer information seeking.Methods . We analyzed 4 categories of breast cancer–related Internet search queries from 2010 to 2013 in the United States.Results . Compared with the preceding 6 weeks, general information queries were 112% (95% confidence interval [CI], 79–146) higher the day of the announcement and remained 35% (95% CI, 22–49) higher over the week after the editorial. Risk assessment queries were 165% (95% CI, 110–222) higher the day of the announcement and 52% (95% CI, 31–75) higher across the week. Genetics and treatment queries showed little volume before the announcement but increased 2154% (95% CI, 1550–7076) and 9900% (95% CI, 3196–1, 064, 000) the day of, respectively, and remained higher across the week (812% [95% CI, 402–3913] and 2625% [95% CI, 551–317, 000]). All query categories returned to normal volumes by the beginning of the second week.Conclusion . Jolie's unique announcement spurred significant information seeking about breast cancer genetic testing and treatment procedures, although the surge in queries returned to preannouncement levels after 1 week. Future research should apply digital methods to advance our understanding of cancer information seeking in the digital age.